Factors Causing Pending Claims BPJS Health Inpatient Use Improving Claim Quality At Welas Asih Regional Hospital - Maulana, Rifqi; Sari, Irda (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
BPJS Kesehatan claims are a crucial component of the continuity of hospital services, yet pending claims are still common. This study aims to identify the factors causing pending inpatient claims at Welas Asih Regional Hospital and understand the obstacles in the claims submission process. The main problems include incomplete supporting documents, mismatched diagnoses, and verification challenges from BPJS. The study used descriptive qualitative methods through interviews, observations, document reviews, and analysis of 521 pending claim files. The results indicate that the largest causes of pending claims stem from BPJS verification (57.39%) and coding (28.60%), while administrative issues account for only a small portion. Good internal coordination between units allows most claims to be resolved without escalation to BPJS. The study concluded that improving the completeness of medical records, coding training, understanding regulations, and reviewing multiple documents are effective strategies to reduce pending claims and increase the efficiency of the BPJS claims process at Welas Asih Regional Hospital.